SCIENTIFIC ARTICLES DEPICTION OF THE ROLE OF THE FAMILY FOR PREVENTING INFECTION OF TB (Tuberculosis) LUNG DISEASE IN WEST LOMBOK ON 2013 - Supinganto, Agus; Metri, I Ketut; Supriyanto, S (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Affection in the family will produce an emotional atmosphere that affect the health of the family members themselves positively, including in the prevention of Tuberculosis disease infection. This study aimed to identify the role of the family to prevent the infection of TB (Tuberculosis) in West Lombok lung disease so that this research can be useful both theoretically and practically.This study used a descriptive survey design approach household survey (Household Survey). The populations in this study were all families with a family member suffering from pulmonary tuberculosis by BTA (+) in West Lombok, which 563 people in 2011. The sample quantities of this study are 85 by using purposive sampling method. While the data collection instrument using the checklist.Data is presented in narrative form, frequency distribution tables and percentages. The results showed that the role of families in preventing infection of TB disease in West Lombok ( 44.71 % ) were in the poor category , ( 29.02 % ) families identify health problems family members , ( 44.12 % ) families make the decision to take action appropriate health for the family . (74.12%) families providing care to family members, (31.76%) modifying the home environment to improve the health of the family, and (83.53%) Utilize family health care facility